"I Didn't Know I Was Isolated Until I Wasn't Isolated Any More": The Use of Groups in Qualitative Psychology Research. (February 2014) - Lavie-Ajayi, Maya
This article explore the use of groups as one way of conducting political research within psychology, and challenging the overindividualistic approach of most psychological studies and theories. Calling on her own research studies, the author explores the possibilities presented by groups to create social spaces, in which meaning and narratives are co-constructed in dynamic negotiation. Working with groups in a participatory and democratic process can create rich, deep, and varied knowledge that highlights the wider context of individual experiences. To achieve this aim, personal and group reflexivity must be a part of the research process. In so doing, groups can offer ways to disrupt the dichotomy and change the power relationship between researcher and participant, as groups offer a different composition of research relations, not limited to just two hierarchal positions. The interactions between participants can create a collective mosaic: a fusion of points of view, experiences, and understandings.